Risks and complications associated with ovarian stimulation for fertility treatment - Baumgarten, Miriam N. (2018)
Almost all fertility treatment involves ovarian stimulation. This can be in the form of ovulation induction in women with anovulation or controlled ovarian stimulation for in vitro fertilisation treatment. The stepwise approach to fertility treatment in most cases it will be safe and successful. In certain cases, it might be however ineffective or related with adverse health outcomes for the woman causing significant distress for the couple and the treating clinicians.